Finance in Africa Uncertain times, resilient banks: African finance at a crossroads (European Investment Bank, 2023)
The Finance in Africa report emphasises the challenges faced by the African banking sector - including the impact of recent shocks, such as the COVID-19 crisis and Russia's invasion of Ukraine - and the importance of gender diversity in business and banking. The report also discusses the need for international support and sustainable finance to advance economic development and climate change in Africa. It provides insights into the financial conditions, banking sector performance, and investment trends in the region. It covers the nature of climate finance flows in Africa and the degree of climate risk on bank balance sheets. With the right measures in place, Africa has the potential to overcome its challenges and unlock its true economic potential.